THE STUDY OF LONGITUDINAL AND LATITUDINAL VARIATION OF EQUATORIAL ELECTROJET SIGNATURE AT STATIONS WITHIN THE 96Â°MM AND 210Â°MM AFRICAN AND ASIAN SECTORS RESPECTIVELY UNDER QUIET CONDITIONS. (FUDMA JOURNAL OF SCIENCES, 2021)
Solar quiet current (S_q) and Equatorial Electrojet (EEJ) are two current systems which are produced by electric current in the ionosphere.  The enhancement of the horizontal magnetic field is the EEJ. This research is needed for monitoring equatorial geomagnetic current which causes atmospheric instabilities and affects high frequency and satellite communication. This study presents the longitudinal and latitudinal variation of equatorial electrojet signature at stations within the 96Â°mm and 210Â°mm African and Asian sectors respectively during quiet condition. Data from eleven observatories were used for this study. The objectives was  to determine the longitudinal and latitudinal geomagnetic field variations during solar quiet conditions, Investigate monthly variation and diurnal transient seasonal variation; Measure the strength of the EEJ at stations within the same longitudinal sectors and find out the factors responsible for the longitudinal and latitudinal variation of EEJ. Horizontal (H) component of geomagnetic field for the year 2008 from Magnetic Data Acquisition System (MAGDAS) network were used for the study. The International Quiet Days (IQDs) were used to identify quiet days. Daily baseline values for each of the geomagnetic element H  were obtained.  The monthly average of the diurnal variation was found. The seasonal variation of dH was found. Results showed that: The longitudinal and latitudinal variation in the dH differs in magnitude from one station to another within the same longitude due to the difference in the influence of the EEJ on them.
Keywords: Equatorial Electrojet, Counter Electrojet, Ionosphere